P734 What do guys know about syphilis anyways?. (14th July 2019) - Gesink, Dionne; Connell, James; Kimura, Lauren
Abstract : Background: Syphilis rates among gay, bisexual, and other men who have sex with men (gbMSM) have increased in Toronto, Canada, since the early 2000s. Half of syphilis cases are co-infected with HIV. Enhanced sexual health resources in the downtown neighbourhoods with elevated syphilis rates (core area) have not brought syphilis transmission under control. Our objective was to explore gbMSM attitudes, beliefs and knowledge of syphilis to inform syphilis intervention strategies. Methods: In-depth interviews were conducted with 31 gbMSM who lived, worked, or socialized in Toronto, Canada, in June and July of 2016. Interviews ran 60 to 90 minutes and had three sections. This analysis uses data from the third section, which explored what participants knew about syphilis and the syphilis epidemic in Toronto. Theoretical saturation for this analysis was reached before interviews were completed. Thematic analysis was used to analyze interviews. Transcripts were read and re-read, then coded. Codes were compared across participants then grouped into categories; categories were grouped into themes. Results: Participants knew little about syphilis and did not realize syphilis was epidemic in Toronto. Syphilis was perceived as a curable inconvenience and dismissed, while HIV was perceived as life-changing. Participants did know something about HIV and some STIs other than syphilis. Participants who lived through the 80's and 90's identified anal sex as a high-risk sexual activity and perceived sex as potentially lethal; consequently, sex was loaded with stigma, burden and shame. In backlash, some participants described a new social expectation that gay men should have a lot of good sex, where good sex is sex without a condom, and having good sex is a greater concern than acquiring an STI that can be cured or lived with. Conclusion: Dismissive attitudes towards syphilis could explain why syphilis epidemics persist. Interventions shifting gbMSM relationship with sex and STI testing should be explored. Disclosure: No significant relationships.